Comparative Evaluation of Boric Acid Gel versus Chlorhexidine Gel in the Treatment of Chronic Periodontitis: Randomized, Placebo-Controlled Clinical Study - Mamajiwala, Alefiya (Contemp Clin Dent, 2019)
BACKGROUND: Over the years, various antimicrobials have been tried and tested in the treatment of periodontitis. Chlorhexidine (CHX) has emerged as the gold standard. In recent years, trend has shifted toward the use of agents with antibacterial, anti-inflammatory, and osteoblastic activity. Boric acid (BA) is one such agent which possess all such properties and thus been evaluated in the treatment of periodontitis. AIM AND OBJECTIVE: The aim of the study is to compare and evaluate the efficacy of 0.75% BA gel versus 1% CHX gel as an adjunct to scaling and root planing in patients with chronic periodontitis both clinically and microbiologically. MATERIALS AND METHODS: The present study was a randomized, placebo-controlled clinical trial where 45 systemically healthy patients with chronic periodontitis were included in the study. About 15 patients each were divided into three groups, that is, Group I received BA gel, Group II received CHX gel, and Group III received placebo gel as a local drug delivery agent. Clinical parameters such as gingival index, plaque index, modified sulcus bleeding index, probing pocket depth, and clinical attachment level were evaluated at baseline and 6-month follow-up. Microbiological analysis to check for mixed anaerobic flora was done using subgingival plaque samples at baseline and 3 months after treatment. RESULTS: Significant reduction was seen in all clinical parameters in both BA and CHX gel groups as compared to control group (P < 0.05). However, on comparing BA gel group with CHX gel, the results were statistically insignificant (P > 0.05). CONCLUSION: BA gel and CHX gel both were equally effective in improving the clinical and microbiologic parameters in patients with chronic periodontitis when used as a local drug delivery agent.